PROVE IDRAULICHE SU UN SEMOVENTE IRRIGUO - Giuseppe Taglioli; Angelo Fabbri (Journal of Agricultural Engineering, 2007)
The correct management of the irrigation is a well known factor of success in agriculture, even as regard the water saving. As a consequence it was tested here a very common medium sized hose-reel irrigation machine, known in Italy as rotolone. Several hydraulic and technical aspects were investigated, in two tests on a 3 ha field: – the hydraulic distribution on the field, measured by means of 55 rainfall meter; – the uniformity of the forward speed and the effectiveness of the controller; – the effect of the standstill times on distribution quality; – the hydraulic performance declared by the manufacturer; – the water consumption, the manpower requirements; – the quality of irrigation. Moreover a theoretical analysis of the best overlapping between the range of two adjacent sprinkler was developed. The tests have shown the importance of the regularization of the backward speed: in lack of this the variations can reach the value of 70%. The value of 85% in overlapping of wetted areas, recommended by manufacturers, was theoretically justified. The measured mean range, at the recommended pressure, was 10% lower than declared by manufacturer. The rain hourly intensity was too high for the needing of the clay soil of the field. The jet spraying was coarse in relationship to the clay fraction of the soil but not for the crop (maize). The hose-reel irrigation machine examined here, can maintain an high level of feasibility if some improvement were adopted.